Network Coordinator Perceptions of Early Childhood Community Systems Building and Development Efforts - Tuyet Mai Ha Hoang; Brandie Bentley; Karen V. Jenkins; Crystal A. Reinhart; Gloria A. Sugg; Karen M. Tabb (Children, 2025)
Background: Networks for building and developing community systems to support early childhood rely on the volunteer efforts of organizations and the leadership of coordinators to unite relevant stakeholders. Aims: The purpose of this study was to explore the perspectives of network coordinators from 10 different communities participating in the All Our Kids Early Childhood Networks (AOK Networks) to identify the successes and barriers involved in implementing effective early childhood systems. Methods: We conducted two focus group interviews with 10 participants who worked as network coordinators in public health district offices. A semi-structured focus group interview guide was used to examine community coordinators’ perceptions related to lessons learned with community systems development efforts around early childhood outcomes. All interviews were audio recorded and transcribed verbatim. Thematic network analysis was used to analyze all focus group data. Results: Three salient themes were identified from interviews with network coordinators: (1) respective strengths of the AOK Networks system building efforts; (2) challenges for coordinators, such as burnout; and (3) the importance of the networks’ role within the community. Conclusions: This study contributes to the existing literature by identifying supportive and hindering factors that impact the implementation process to sustain long-term impact of early child community systems building. The findings can be useful for other ongoing government partnerships and community-based programs that use networks and system building strategies across the US.